A meso-scale model toward concrete water permeability regarding aggregate permeability. (20th November 2020) - Liang, Minfei; Feng, Kun; He, Chuan; Li, Yuqiang; An, Lin; Guo, Wenqi
Highlights: A sophisticated meso-scale model was developed using an efficient algorithm. The effect of aggregate permeability on concrete water permeability is illustrated and estimated. The importance of aggregate permeability is illustrated for precise meso-scale model. Abstract: The permeability of natural aggregate is close to cement mortar with relative lower w/c ratios, therefore when calculating the overall concrete water permeability, the effect of aggregate permeability cannot be neglected. This paper presents a sophisticated 3D three phase meso-scale model based on an efficient method of generating random ellipsoidal particles within confined cylindrical space. The meso-scale model considers concrete as the combination of mortar, aggregate and interfacial transition zone, and is used to characterize the permeability of concrete. Furthermore, a series of permeation experiments of concrete with different w/c ratios and aggregate volume fractions are conducted to exemplify the effects of aggregates on concrete water permeability and provide parameters and verification for numerical models. The effects of aggregate permeability on concrete water permeability is evaluated based on both experimental and numerical results. And the permeability coefficient of aggregate adopted in the experiment is estimated reasonably and incorporated into further numerical predictions of concrete water permeability. By comparing the experimental and numerical results, the applicability of meso-scale model proposed here is validated and the effects of aggregate on water permeability of concrete with different w/c ratios vary from each other, depending on the ratio of water permeability of aggregate and mortar.